Demonetisation : claims and reality - Edited by Atul Sarma (New Delhi Aakar, 2019)
The basic motivation for bringing this booklet is to put together our initial understanding of the rationale of this drastic policy measure and its outcomes on the economy and the society and to see how our initial understanding compares with the outcomes that have indeed become much clearer and even quantifiable at the close of almost two years.
Keywords: Monetary policy; Economic history